Faktor Pengembangan Organisasi Dan Fungsional Di SDN 16 Air Tawar, Kota Padang - Destia Putri Cahyani (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The purpose of this study was to examine the variables that influence the development of the school organization at SDN 16 Air Tawar, Padang City. This study used observation and interviews with the principal and teachers. The results of the study show that there are three factors that influence school organizational development: internal factors, external factors, and functional factors. Internal factors include communication, cooperation, and student openness. External factors include assistance from the Education Office, school supervisors, and government policies. From the principal, teachers, administrative staff, to school guards, every member of the organization plays an important role in maintaining the sustainability of the organization. In addition, regulations, technology, economics, and the socio-cultural environment all contribute to organizational development. This study confirms that cooperation and participatory leadership are essential for making schools competitive and flexible.